CHALLENGES IN CYBERSECURITY AND WORLDWIDE INFORMATION SECURITY - Bozorov Akmal Isroilovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In today’s digital era, cybersecurity has become one of the most critical global issues. The rapid development of technology, widespread internet access, and increasingly advanced cyberattacks have exposed individuals, organizations, and governments to serious information security threats. This article examines major challenges in global information protection, including cybercrime, data breaches, the vulnerability of critical infrastructure, and violations of personal privacy. It also discusses various strategies, security frameworks, and international cooperation efforts aimed at reducing cyber risks. The study highlights that ensuring effective cybersecurity and protecting sensitive information in a global context requires a combination of technological solutions, strong policy regulations, and increased public awareness.